LAW ENFORCEMENT AGAINST CHILDREN WITH VIOLENCE - Juhriati; Jufrin; Muhammad Amin (Awang Long Law Review, 2023)
The purpose of this research is first to describe the implementation of law enforcement against child victims of intercourse accompanied by violence in the Bima Kota Police PPA Unit; second, to describe the obstacles in law enforcement against child victims of violent intercourse at the Bima Kota Police PPA Unit. Empirical legal research methods (non-doctrinal), case and policy approaches, using data collection, documentation, observation and interviews and integrating with literature review of legal documents relevant to the object under study, and analyzed descriptively. The results of the study show, First, the implementation of law enforcement against child victims of violent intercourse at the Bima City Police Unit PPA is in accordance with applicable laws and regulations using the Criminal Procedure Code and the SPPA, where at the investigation level it is carried out starting with an initial examination or interrogation of witnesses who can provide clues to the incident. Then a post mortem et review was carried out on the victim's child to identify injuries to physical violence. Then the crime scene was processed at the scene to confirm other clues. Second, obstacles in law enforcement against child victims of sexual intercourse, (1) Witnesses who are still children and find it difficult to communicate during the examination process. Especially if the key witness is a child who is still traumatized by the events he witnessed. (2) There were no witnesses who saw them directly and the witnesses did not want to come to provide information. (3) There were difficulties in uncovering the cause of death of the victim's child because in the jurisdiction of the Bima City Police there were no forensic experts so they had to carry out an autopsy at the Bayangkara Hospital in Mataram. (4) There is no expert psychologist witness accompanying the child witness in proving the quality of the testimony given by the child witness.